Makna Pendapatan Bagi Petani Tambak Terhadap Kerugian Yang Dialami Ketika Lahan Pertambakan Mengalami Kebanjiran - Naabilah Surrohmawati; Anita Handayani (Universitas Muhammadiyah Gresik, 2022)
Background - Tambak Beras is one of the villages located in Cerme District, Gresik Regency, East Java Province. The source of livelihood for the residents of Tambak Beras Village is aquaculture. The pond farmers in Tambak Beras Village still use a very simple theory. Objective - This study aims to determine pond farmers in interpreting the income against losses due to the phenomenon of flooding. By using 5 informants including 1 (one) informant who is the head of a group of fish farmers in the village of rice ponds as gatekipper and 4 (four) other informants in accordance with the criteria for determining the informant. Design/Methodology/Approach - The test was conducted using qualitative research with descriptive analysis methods. Findings - The results of the study show that: (1) for the owner of the pond land, income is a gain obtained from eachbusiness according to the type of work. (2) the majority of farm farmers who rent ponds and manage individually interpret the income as a net calculation obtained during one harvest period after deducting initial venture capital, operational costs, unexpected cost, so that the income they receive is purely as profit from the period. (3) whereas according to the majority of mustard or pond workers interpret the income as wages obtained even though not necessarily how much the nominal because it depends on the profit sharing system provided by pond farmers who have land. Research implications - Based on the results of the interviews, it can be described to the parties who are pond farmers whose ponds are flooded, resulting in losses and no income received by pond farmers. Research limitations - This research was only conducted on pond farmers in Cerme District, Gresik Regency, East Java Province.